Utilization of control technology for mushroom production houses using the internet of things (IoT) in SMEs Omah Jamur Ungaran - Nur Islahudin; Herwin Suprijono; Rindra Yusianto; Helmy Rahadian (Community Empowerment, 2022)
Indonesians are currently well familiar with oyster mushroom cultivation. However, there are various issues with cultivation. Omah Jamur Ungaran in Semarang Regency likewise has same problem. The issue is that the mushroom house's production is not optimum because controlling humidity is still done manually, by turning on the pump if the temperature and humidity are not ideal. This causes the mushroom house's humidity to fluctuate. Moreover, the pump's electrical consumption is erratic. This service activity's objective is to provide an automatic device to control humidity and temperature in the mushroom house for optimal mushroom production. The method is to employ IoT technology. The community service determined that the temperature and humidity management system in the oyster mushroom production room can be automated, with the sprayer pump turning on when the temperature reaches 29º C and off when the temperature reaches 28.5º C. Furthermore, using the Thingspeak platform, MSME owners may automatically monitor the temperature and humidity of the mushroom production room.